Հայաստանը անդրկովկասյան–մերձավորարևելյան աշխարհաքաղաքական տարածաշրջանի գործոն - Հովհաննիսյան, Նիկոլայ («Զանգակ - 97»)
Armenia after gaining an independence in 1991, step by step became а significant factor of the Transcaucasian-Middle Eastem geopolitical region. Its functions of a factor Armenia is realizing on three levels.The First level - geopolitical factor. On this level Armenia is playing an important role in relations with Russia, Iran, as well as Georgia. We qualify that role as constructive. The USA and the leading European states, China and other countries are more and more realistically appreciating the significance of Armenia in decision of Caucasian and Middle Eastern regional problems.
Keywords: Պատմություն; Քաղաքականություն